(untitled) (Proceedings of International Educators Conference, 2023)
This paper is based on basic information about idioms that are completely crucial in English and Uzbek languages. Also in this article, essential information is given about the color idioms in English and their definitions and clarified the ways of translation of the English color idioms into Uzbek. Here also analyzed the translations of English and Uzbek color idioms with some examples. Actually, the meaning of these color idioms may differ according to culture, language, customs and traditions, religion, and situations.